Systemic delivery of microRNA-21 antisense oligonucleotides to the brain using T7-peptide decorated exosomes - Kim, Gyeungyun; Kim, Minkyung; Lee, Youngki; Byun, Jung Woo; Hwang, Do Won; Lee, Minhyung (Journal of controlled release, 2020)
Antisense miRNA oligonucleotides against miR-21 (AMO-21) have a therapeutic potential for treatment of glioblastoma. However, glioblastoma-targeted delivery through systemic injection requires development of an efficient targeting carrier. For this purpose, a glioblastoma-targeting carrier was developed using the T7 peptide and exosomes. The transferrin receptor is overexpressed on the surface of glioblastoma cells, and T7 is a transferrin receptor-binding peptide. A T7 peptide-decorated exosome (T7-exo) was produced by incorporation of T7 into the exosome membrane as a fusion protein of T7 and Lamp2b. As a control, rabies virus glycoprotein (RVG) peptide targeting brain neuron cells was incorporated into the exosome membrane. AMO-21 was loaded into the exosomes by electroporation. In vitro studies of AMO-21 delivery showed that T7-exo had a higher delivery efficiency to C6 glioblastoma cells than unmodified exosome (Unmod-exo) and RVG-decorated exosome (RVG-exo). For in vivo delivery studies, T7-exo with AMO-21 was delivered into intracranial glioblastoma rat models by intravenous injection through the tail vein. The results showed that T7-exo delivered AMO-21 into the brain more efficiently than Unmod-exo and RVG-exo. In addition, delivery of AMO-21 using T7-exo reduced the miR-21 level in the glioblastoma efficiently. Reduction of miR-21 by AMO-21 induced the expression of PDCD4 and PTEN in tumors, resulting in reduction of tumor sizes. Taken together, these findings indicate that T7-exo is an efficient carrier of AMO-21 into the glioblastoma and may be useful in development of glioblastoma therapy. [Display omitted]